Garden policies of the Warsaw housing cooperative: the garden and the right to the city - Matysek-Imielińska, Magdalena (Polskie Studia Krajobrazowe, 2019)
The article analyzes the project of green spaces to accompany a 1920s residential development in Warsaw. The estate was intended to provide a housing minimum for the poorest inhabitants, as well as educate workers how to live an urban lifestyle. It was presumed that access to greenery, nature, a site of leisure and the smell of flowers cannot be a privilege of the bourgeoisie. Thus, the garden policy proved an emancipatory gesture, an assertion of the right to the city and a means of forging civic mindsets and attitudes. The author asks whether the innocent gardens became workshops in Sennett’s understanding, shaping principles and rituals of cooperation, and examines how they helped to promote a new citizen in a new estate.en